PENGARUH PERSEPSI KEADILAN TERHADAP KEPUASAN PENILAIAN KINERJA - Chusminah, Chusminah (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
This research aims to analyze the influence of perceptions of fairness on satisfaction of performance appraisal. The research method used quantitative descriptive analysis method by testing a sample of 100 employees of the second largest Foundation of Islamic Education in Yogyakarta. Data analysis techniques using SPSS version 21. Findings in this study indicate that there is an effect of fairness on satisfaction of performance appraisal. The implication of this study is that efforts to create employee satisfaction in performance appraisal are inevitable to always be realized because they will be indicators of the effectiveness or failure of the performance appraisal function carried out by an organization. The limitations of this study are limited to one organization so that the results of the study cannot be generalized to other organizational conditions, both similar and different. Keywords: fairness perception, performance appraisal satisfaction